2016
DOI: 10.1007/s00300-016-2014-y
|View full text |Cite
|
Sign up to set email alerts
|

Diatom communities in the High Arctic aquatic habitats of northern Spitsbergen (Svalbard)

Abstract: As High Arctic environments are particularly sensitive to global and regional climate changes, a growing number of studies have focused on that region. It has been shown that living and fossil diatoms can be successfully used to track environmental changes in polar habitats. Nevertheless, the diatom flora of many Arctic areas remains unknown. The present study set out to examine the diatom flora in the rarely visited and near-pristine zone of northern Spitsbergen. Examination by light and scanning electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…frustulum , and N . perminuta ), common Arctic taxa that dominate assemblages at sites with greatly elevated nutrients [ 73 , 74 ] and more alkaline pH [ 78 , 83 ], are present in high relative abundances throughout the Moraine Pond record.…”
Section: Discussionmentioning
confidence: 99%
“…frustulum , and N . perminuta ), common Arctic taxa that dominate assemblages at sites with greatly elevated nutrients [ 73 , 74 ] and more alkaline pH [ 78 , 83 ], are present in high relative abundances throughout the Moraine Pond record.…”
Section: Discussionmentioning
confidence: 99%
“…The largest grouping of diatom samples belongs to biotype 2 comprising a diverse group of lakes and ponds. The small benthic fragilarioid taxa typical of this biotype are one of the most opportunistic and ubiquitous diatom groups reported in the literature (Schmidt, Kamenik, Lange-Bertalot, & Klee, 2004) and are commonly reported in lakes across the circum-Arctic (Douglas & Smol, 1995;Griffiths, Michelutti, Sugar, Douglas, & Smol, 2017;Laing, Pienitz, & Smol, 1999;Lehnherr et al, 2018;Pienitz et al, 1995;Rühland et al, 2003;Saulnier-Talbot, Larocque-Tobler, Gregory-Eaves, & Pientiz, 2015;Schmidt et al, 2004;Smith, 2002;Weckström et al, 1997;Zgrundo, Wojtasik, Convey, & Majewska, 2017). The generalist nature of these benthic diatoms results in their occurrence in a wide range of habitats where they are able to tolerate low light conditions, as, for instance, under ice (Lotter & Bigler, 2000) or in turbid waters (Karst-Riddoch, Pisaric, Youngblut, & Smol, 2005).…”
Section: Lake Diatom Biotypesmentioning
confidence: 99%
“…Diatoms need silica for cell growth and since conductivity increased throughout the monitoring period, indicating an increased ion input (e.g. silica), this increase in conductivity might explain the increase in diatom biomass (Ryves et al., 2002; Zgrundo et al., 2017). Additionally, Lehnherr et al.…”
Section: Discussionmentioning
confidence: 99%
“…Diatoms need silica for cell growth and since conductivity increased throughout the monitoring period, indicating an increased ion input (e.g. silica), this increase in conductivity might explain the increase in diatom biomass (Ryves et al, 2002;Zgrundo et al, 2017). Additionally, Lehnherr et al (2018) and Michelutti et al (2020) showed a shift from benthic diatoms to planktonic diatoms in a High Arctic lake in Canada as a result of a declining ice cover.…”
Section: The Total Nitrogen and Phosphorus Levels In Langemandssø Andmentioning
confidence: 99%